2020
DOI: 10.3390/plants9091219
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of Betalains: A Review

Abstract: Anthocyanins, betalains, riboflavin, carotenoids, chlorophylls and caramel are the basic natural food colorants used in modern food manufacture. Betalains, which are composed of red–violet betacyanin and yellow betaxanthins, are water-soluble pigments that color flowers and fruits. Betalains are pigments primarily produced by plants of the order Caryophyllales. Because of their anti-inflammatory, cognitive impairment, anticancer and anti-hepatitis properties, betalains are useful as pharmaceutical agents and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 115 publications
1
55
0
6
Order By: Relevance
“…Furthermore, the ability of betalain from beetroot extract in inhibiting hexokinases enzyme for controlling blood sugar level has been reported by Kabir's group, confirming its potential as an anti-diabetic compound [26,27]. Moreover, the investigation of betacyanin from beetroot as an anti-cancer compound through in vitro studies showed favorable inhibition to various cancer cells in breast, colon, stomach, and lung [20,25]. The betalains also have been reported to have an ability in chelation of inner cations that the parasites need [20].…”
Section: Betalain Dye and Its Utilization In Dye-sensitized Solar Celmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, the ability of betalain from beetroot extract in inhibiting hexokinases enzyme for controlling blood sugar level has been reported by Kabir's group, confirming its potential as an anti-diabetic compound [26,27]. Moreover, the investigation of betacyanin from beetroot as an anti-cancer compound through in vitro studies showed favorable inhibition to various cancer cells in breast, colon, stomach, and lung [20,25]. The betalains also have been reported to have an ability in chelation of inner cations that the parasites need [20].…”
Section: Betalain Dye and Its Utilization In Dye-sensitized Solar Celmentioning
confidence: 77%
“…They noted that betacyanins have inhibition percentage of up to 50% while betaxanthins were up to 60%. The good antioxidant activities of betalains then can bring benefit in inhibiting lipid oxidation to prevent cardiovascular diseases [21,25]. Furthermore, the ability of betalain from beetroot extract in inhibiting hexokinases enzyme for controlling blood sugar level has been reported by Kabir's group, confirming its potential as an anti-diabetic compound [26,27].…”
Section: Betalain Dye and Its Utilization In Dye-sensitized Solar Celmentioning
confidence: 89%
See 1 more Smart Citation
“…In the rat model of Parkinson’s disease induced by combined administration of tacrine, haloperidol and reserpine, red beet (100, 200 and 300 mg/kg) protected against behavioral changes and ameliorated oxidative stress [ 243 ]. These results indicate that betanin may have the ability to prevent or delay the progress of neural death in PD [ 244 ].…”
Section: Health Benefitsmentioning
confidence: 99%
“…The radioprotective effect was ascribed to the antioxidant activity of the betalains and modulation of the immune system by these compounds [ 281 ]. Therapeutic applications of betalains have been summarized in a recent review [ 244 ].…”
Section: Health Benefitsmentioning
confidence: 99%